PATICIPATION IN THE IMPLEMENTATION OF THE MANUAL AS A GUIDELINE FOR THE WORK OF THE DEPARTMENT UNDER THE MINISTRY OF PUBLIC HEALTH - Matian, Pachara (Journal of MCU Nakhondhat, 2022)
This academic work There is a demand object to study and compile legal, regulations, announcements, circulars related to internal welfare and business welfare in the government and to create a manual for the welfare operations of the service unit under the Office of the Permanent Secretary of Public Health. In order to properly manage welfare within the department. By proceeding between May 2019 and December 2019 and in operation there are 4 steps, namely Step 1, Collect data. And review the implementation of internal welfare and business welfare of the service unit under the Office of the Permanent Secretary for Public Health. Step 2, Drafting of the Welfare Service Manual under the Office of the Permanent Secretary for Public Health By holding a working group meeting of the Juristic person of the Legal Division, the Law Division, the Law Enforcement Group, the Discipline and the Moral System, the Legal Representative from the Provincial Health Office total of 20 people to determine the content and format of the guide. Analyze content and create draft manuals. Step 3. Create a manual by collecting data from the content analysis in step 2. Let’s compose it into a system. Step 4. Create a handbook in a book and complete the electronic book file. Give to trainees according a total 1,200 people and disseminating information on the website of the Public Health Lawyers Association (www.mophlawyer.com). The results show that The welfare operation manual of the service unit under the Office of the Permanent Secretary for Public Health. There are a total of 6 chapters, consisting of 1) The importance and origin of the welfare operation 2) Regional welfare arrangements 3) Guidelines about internal welfare 4) Guidelines for business welfare 5) Financial and property management and 6) Examples of welfare processing forms